Faktor-Faktor Yang Mempengaruhi Tingkat Partisipasi Angkatan Kerja (TPAK) Kabupaten/Kota Di Kalimantan Barat - B01112030, JONO (Jurnal Curvanomic, 2016)
the labor force participation rate of is a measure to determine how many people who intend to engage in economic activities. The aim of this research is to find out factors that affect the labor force participation rate in West Kalimantan during the period from 2010 to 2014. The data analysis technique used was multiple regression. Partially, wages, had a significant effect on the labor participation rate with a significance level of 0.0008<0.05; age had a significant effect on the labor participation rate with a significance level of 0.0002<0.05; education had a significant effect on the labor participation rate with a significance level of 0.0000<0.05; wages, age, education simultaneously had a significant effect on the labor participation rate with a significance level of 0.000000<0.05 Keywords: Labor Force Participation Rate, Wage, Age, Education